1999
DOI: 10.1038/sj.gt.3300837
|View full text |Cite
|
Sign up to set email alerts
|

Cationic lipid-mediated transfection of cells in culture requires mitotic activity

Abstract: Cationic lipid-based delivery systems such as lipoplexes or aphidicolin exhibited 20-fold lower reporter gene activity stabilized plasmid-lipid particles (SPLP) represent a safer than asynchronous control cells upon incubation with lipoalternative to viral systems for gene therapy applications.plexes. When cells arrested in the G1 phase were allowed We studied the impact of cell cycle status on the efficiency to proceed though the cell cycle in the presence of the lipoof transfection of human ovarian carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(156 citation statements)
references
References 28 publications
8
148
0
Order By: Relevance
“…Since it is believed that the majority of the DNA enters the cell nucleus during mitosis, we synchronized the myoblasts with aphidicolin 27,28 to verify the effect of cell cycle synchronization on PEI adenofection. No significant enhancement of transfection efficiency was observed (Table 1).…”
Section: Additional Reagents Could Not Enhance Pei Adenofectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is believed that the majority of the DNA enters the cell nucleus during mitosis, we synchronized the myoblasts with aphidicolin 27,28 to verify the effect of cell cycle synchronization on PEI adenofection. No significant enhancement of transfection efficiency was observed (Table 1).…”
Section: Additional Reagents Could Not Enhance Pei Adenofectionmentioning
confidence: 99%
“…51 This explains why rapidly dividing cells are more readily transfected. To try to enhance nuclear entry of plasmid DNA during mitosis, we synchronized the myoblasts with aphidicolin 27,28 but no enhancement of transfection was observed. Synchronizing the cells at mitosis when the nucleus is disrupted could perhaps be more efficient in enhancing transfections than synchronizing the cells in G1/S as we did.…”
Section: Figure 4 Expression Of Adenoviral Proteins In Cells After Pementioning
confidence: 99%
“…This finding is in line with the fact that postmitotic cells have a lower expression rate after lipoplex transfection than highly mitotic (tumor) cells. 14 The cationic liposomal preparations LipofectAmine and DOTAP were further tested for efficiency of cell transduction in the presence or absence of fetal calf serum (FCS) in the culture medium. NT2 cells and NT2N neurons were efficiently transfected with the pCMV-luc vector in medium without FCS (Optimem; Gibco BRL), while addition of 10% FCS (Sigma, Deisenhofen, Germany) drastically reduced the efficiency of transduction in both cell types.…”
Section: Units (Rlu)/mg Protein) Control Nt2 Cells Transfected With mentioning
confidence: 99%
“…Mortimer et al 14 showed that mitotic cells have increased transfectability compared with the low transfection rates in postmitotic cells. In agreement with these findings, our studies showed that the transgene expression in postmitotic NT2N neurons was four-fold lower than in undifferentiated NT2 cells.…”
Section: Units (Rlu)/mg Protein) Control Nt2 Cells Transfected With mentioning
confidence: 99%
“…The positively charged head-group was generally believed to allow interactions between the cationic lipids, the negatively charged DNA, as well as cell membrane through charge/charge interactions. 39,40 The presence of nitrogen and oxygen atoms in the heterocyclic ring might further contribute to this charge/charge interaction of liposome and plasmid DNA and stabilize the binding between the cationic liposomes and DNA.…”
Section: Discussionmentioning
confidence: 99%